(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Gmelina arborea seed was investigated. The oil was obtained by solvent extraction using petroleum ether. The percentage oil yield was 52.56%. Proximate analyses showed that the seed contained 4.15% ash, 5.09% Nitrogen,31.81%crude protein, and 5.71%moisture. The specific gravity and refractive index were found to be 0.89 and 1.441, respectively. Characterization of the oil showed that the oil had an iodine value of 60.28g/100gm, saponification value of 84.15mgKOH/g, acid value of 2.917mg/g, 1.45%mg/g free fatty acid, and percentage of unsaponifiable matter 1.54. The iodine and saponification values showed that the oil has a low degree of unsaturation, thus non-drying oil, and has high molecular, making the oil suitable for human consumption. Minerals were also determined by Atomic Absorption Spectroscopic method. Fatty acids of oil are analyzed using gas chromatography to detect the potential source of oil. Seventeen fatty acids were found in the seed oil; the most abundant were Oleic Acid Methyl Ester(C18:1n9c) and Linoleic Acid Methyl Ester(C18:2n6c). Linoleic Acid Methyl Ester (an omega-6 fatty acid) and α-Linolenic acid Methyl Ester (an omega-3 fatty acid) are essential for human health. Amino acid results showed the protein contained and quantities of the most crucial amino acids. Eighteen types of amino acids were found in the seed, and the sources are rich in Glutamate, Aspartate, Serine, Glycine, Alanine, Tyrosine, and Valine. The other amino acid is also found in reasonable quantities. The study aimed to evaluate the nutritional level of seeds in livestock feed.